New species of Dorcopsinema and Paralabiostrongylus (Nematoda: Chabertiidae: Cloacininae) from Indonesia, with a key to species of Dorcopsinema - Purwaningsih, Endang (Zootaxa, 2014)
Two new species of nematodes (Chabertiidae: Labiostrongylinea) from Dorcopsis muelleri in Raja Ampat Island, Papua, were described and figured. Dorcopsinema longispicularis sp.nov.is most similar to D. simile, but can be distinguished from it in being a smaller worm with longer spicules and a relatively longer oesophagus, as well as in the form of the posterior lip of the genital cone, the form of the spicule tips and the spiked tip of the female tail. Paralabiostrongylus rajampatensis sp. nov. differs from its congener, P. bicollaris, in having the deirids and excretory pore at about the same level, and in the form of the dorsal ray, with lateral branches proximal to the bifurcation of the dorsal trunk, the relatively longer spicule with ala extending to the tip and the form of the posterior lip of the genital cone.